Banded Charnockite: The Result of Crustal Magma Generation, Piecemeal Emplacement, and Fluid-Driven Mineral Replacement in High-Grade Crust (Central Dronning Maud Land, Antarctica) - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Elvevold, Synnøve (The Journal of Geology, 2021)
AbstractOur study of a banded charnockite complex of the Mühlig-Hofmannfjella in Dronning Maud Land, Antarctica, illustrates how the combination of high-temperature (re-)crystallization processes, melts, and volatile fluids leads to complex intrusive, metasomatic, and structural relationships. The igneous complex consists of gently dipping sets of charnockite interlayered with dolerite and leucogranite. The banded complex formed primarily by magmatic processes, but with superimposed modifications by metasomatism. The charnockite has a ferroan composition and contains both orthopyroxene (Fs80?84) and olivine (Fa94?96). Zircon U-Pb dates the emplacement of charnockite at 515 Ma, and inherited zircon cores and negative εNd values of ?3 to ?5 indicate that the age of the source of the magma was about 1100 Ma. Neodymium isotopes were not homogenized during the Cambrian magmatic event, which suggests that the generation and emplacement of the magma took place in separate batches during construction of the banded complex. By contrast, the Rb-Sr system in the charnockite was extensively homogenized, likely because of the superimposed late-magmatic fluid activity, which also produced the bands and networks of leucogranites. These events occurred during the late stages of the assembly of Gondwana, with postcollisional extension and mantle upwelling maintaining a high heat flow.
Keywords: Dronning Maud Land; geologi

Observed interannual changes beneath Filchner-Ronne Ice Shelf linked to large-scale atmospheric circulation - Hattermann, Tore; Nicholls, Keith W.; Hellmer, Hartmut H.; Davis, Peter E. D.; Janout, Markus A.; Østerhus, Svein; Schlosser, Elisabeth; Rohardt, Gerd; Kanzow, Torsten (Nature Communications, 2021)
Floating ice shelves are the Achilles’ heel of the Antarctic Ice Sheet. They limit Antarctica’s contribution to global sea level rise, yet they can be rapidly melted from beneath by a warming ocean. At Filchner-Ronne Ice Shelf, a decline in sea ice formation may increase basal melt rates and accelerate marine ice sheet mass loss within this century. However, the understanding of this tipping-point behavior largely relies on numerical models. Our new multi-annual observations from five hot-water drilled boreholes through Filchner-Ronne Ice Shelf show that since 2015 there has been an intensification of the density-driven ice shelf cavity-wide circulation in response to reinforced wind-driven sea ice formation in the Ronne polynya. Enhanced southerly winds over Ronne Ice Shelf coincide with westward displacements of the Amundsen Sea Low position, connecting the cavity circulation with changes in large-scale atmospheric circulation patterns as a new aspect of the atmosphere-ocean-ice shelf system.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf; meteorologi; oseanografi

The effectiveness of Virkon® S disinfectant against an invasive insect and implications for Antarctic biosecurity practices - Bartlett, Jesamine C; Radcliffe, Richard James; Convey, Pete; Hughes, Kevin A; Hayward, Scott A L (Antarctic Science, 2021)
The flightless midge Eretmoptera murphyi is thought to be continuing its invasion of Signy Island via the treads of personnel boots. Current boot-wash biosecurity protocols in the Antarctic region rely on microbial biocides, primarily Virkon® S. As pesticides have limited approval for use in the Antarctic Treaty area, we investigated the efficacy of Virkon® S in controlling the spread of E. murphyi using boot-wash simulations and maximum threshold exposures. We found that E. murphyi tolerates over 8 h of submergence in 1% Virkon® S. Higher concentrations increased effectiveness, but larvae still exhibited > 50% survival after 5 h in 10% Virkon® S. Salt and hot water treatments (without Virkon® S) were explored as possible alternatives. Salt water proved ineffective, with mortality only in first-instar larvae across multi-day exposures. Larvae experienced 100% mortality when exposed for 10 s to 50°C water, but they showed complete survival at 45°C. Given that current boot-wash protocols alone are an ineffective control of this invasive insect, we advocate hot water (> 50°C) to remove soil, followed by Virkon® S as a microbial biocide on ‘clean’ boots. Implications for the spread of invasive invertebrates as a result of increased human activity in the Antarctic region are discussed.
Keywords: Antarktis; biologi; biosikkerhet; fjærmygg; forurensning; klimaendringer; miljøpåvirkning; økologi; økosystemer

Brominated Flame Retardants in Antarctic Air in the Vicinity of Two All-Year Research Stations - Bengtson Nash, Susan Maria; Wild, Seanan; Broomhall, Sara; Bohlin-Nizzetto, Pernilla (Atmosphere, 2021)
Continuous atmospheric sampling was conducted between 2010–2015 at Casey station in Wilkes Land, Antarctica, and throughout 2013 at Troll Station in Dronning Maud Land, Antarctica. Sample extracts were analyzed for polybrominated diphenyl ethers (PBDEs), and the naturally converted brominated compound, 2,4,6-Tribromoanisole, to explore regional profiles. This represents the first report of seasonal resolution of PBDEs in the Antarctic atmosphere, and we describe conspicuous differences in the ambient atmospheric concentrations of brominated compounds observed between the two stations. Notably, levels of BDE-47 detected at Troll station were higher than those previously detected in the Antarctic or Southern Ocean region, with a maximum concentration of 7800 fg/m3. Elevated levels of penta-formulation PBDE congeners at Troll coincided with local building activities and subsided in the months following completion of activities. The latter provides important information for managers of National Antarctic Programs for preventing the release of persistent, bioaccumulative, and toxic substances in Antarctica.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; menneskelig påvirkning; miljøgifter; miljøovervåking; målinger

First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Trophic and fitness correlates of mercury and organochlorine compound residues in egg-laying Antarctic petrels - Carravieri, Alice; Warner, Nicholas A; Herzke, Dorte; Brault-Favrou, Maud; Tarroux, Arnaud; Fort, Jérôme; Bustamante, Paco; Descamps, Sébastien (Environmental Research, 2021)
Understanding the drivers and effects of exposure to contaminants such as mercury (Hg) and organochlorine compounds (OCs) in Antarctic wildlife is still limited. Yet, Hg and OCs have known physiological and fitness effects in animals, with consequences on their populations. Here we measured total Hg (a proxy of methyl-Hg) in blood cells and feathers, and 12 OCs (seven polychlorinated biphenyls, PCBs, and five organochlorine pesticides, OCPs) in plasma of 30 breeding female Antarctic petrels Thalassoica antarctica from one of the largest colonies in Antarctica (Svarthamaren, Dronning Maud Land). This colony is declining and there is poor documentation on the potential role played by contaminants on individual physiology and fitness. Carbon (δ13C) and nitrogen (δ15N) stable isotope values measured in the females' blood cells and feathers served as proxies of their feeding ecology during the pre-laying (austral spring) and moulting (winter) periods, respectively. We document feather Hg concentrations (mean ± SD, 2.41 ± 0.83 μg g−1 dry weight, dw) for the first time in this species. Blood cell Hg concentrations (1.38 ± 0.43 μg g−1 dw) were almost twice as high as those reported in a recent study, and increased with pre-laying trophic position (blood cell δ15N). Moulting trophic ecology did not predict blood Hg concentrations. PCB concentrations were very low (Σ7PCBs, 0.35 ± 0.31 ng g−1 wet weight, ww). Among OCPs, HCB (1.02 ± 0.36 ng g−1 ww) and p, p’-DDE (1.02 ± 1.49 ng g−1 ww) residues were comparable to those of ecologically-similar polar seabirds, while Mirex residues (0.72 ± 0.35 ng g−1 ww) were higher. PCB and OCP concentrations showed no clear relationship with pre-laying or moulting feeding ecology, indicating that other factors overcome dietary drivers. OC residues were inversely related to body condition, suggesting stronger release of OCs into the circulation of egg-laying females upon depletion of their lipid reserves. Egg volume, hatching success, chick body condition and survival were not related to maternal Hg or OC concentrations. Legacy contaminant exposure does not seem to represent a threat for the breeding fraction of this population over the short term. Yet, exposure to contaminants, especially Mirex, and other concurring environmental stressors should be monitored over the long-term in this declining population.
Keywords: Dronning Maud Land; forurensning; miljøendringer; miljøgifter; ornitologi; petreller; sjøfugler

Multi-decadal trends in Antarctic sea-ice extent driven by ENSO–SAM over the last 2,000 years - Crosta, Xavier; Etourneau, Johan; Orme, Lisa C; Dalaiden, Quentin; Campagne, Philippine; Swingedouw, Didier; Goosse, Hugues; Massé, Guillaume; Miettinen, Arto; McKay, Robert M; Dunbar, Robert B; Escutia, Carlota; et al. (Nature Geoscience, 2021)
Antarctic sea ice has paradoxically become more extensive over the past four decades despite a warming climate. The regional expression of this trend has been linked to changes in vertical redistribution of ocean heat and large-scale wind-field shifts. However, the short length of modern observations has hindered attempts to attribute this trend to anthropogenic forcing or natural variability. Here, we present two new decadal-resolution records of sea ice and sea surface temperatures that document pervasive regional climate heterogeneity in Indian Antarctic sea-ice cover over the last 2,000 years. Data assimilation of our marine records in a climate model suggests that the reconstructed dichotomous regional conditions were driven by the multi-decadal variability of the El Niño Southern Oscillation and Southern Annular Mode (SAM). For example, during an El Niño/SAM– combination, the northward sea-ice transport was reduced while heat advection from the subtropics to the Southern Ocean increased, which resulted in reduced sea-ice extent in the Indian sector as sea ice was compacted along the Antarctic coast. Our results therefore indicate that natural variability is large in the Southern Ocean and suggest that it has played a crucial role in the recent sea-ice trends and their decadal variability in this region.
Keywords: Sørishavet; havis; klimaendringer; klimamodeller; sjøis

Decline in body condition in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean during the 1990s - Cunen, Céline; Walløe, Lars; Konishi, Kenji; Hjort, Nils Lid (Polar Biology, 2021)
Keywords: Sørishavet; hvaler; krill; marin biologi

Sea-ice habitat minimizes grazing impact and predation risk for larval Antarctic krill - David, Carmen L; Schaafsma, Fokje L; van Franeker, Jan A; Pakhomov, Evgeny A; Hunt, Brian P V; Lange, Benjamin A; Castellani, Giulia; Brandt, Angelika; Flores, Hauke (Polar Biology, 2021)
Survival of larval Antarctic krill (Euphausia superba) during winter is largely dependent upon the presence of sea ice as it provides an important source of food and shelter. We hypothesized that sea ice provides additional benefits because it hosts fewer competitors and provides reduced predation risk for krill larvae than the water column. To test our hypothesis, zooplankton were sampled in the Weddell-Scotia Confluence Zone at the ice-water interface (0–2 m) and in the water column (0–500 m) during August–October 2013. Grazing by mesozooplankton, expressed as a percentage of the phytoplankton standing stock, was higher in the water column (1.97 ± 1.84%) than at the ice-water interface (0.08 ± 0.09%), due to a high abundance of pelagic copepods. Predation risk by carnivorous macrozooplankton, expressed as a percentage of the mesozooplankton standing stock, was significantly lower at the ice-water interface (0.83 ± 0.57%; main predators amphipods, siphonophores and ctenophores) than in the water column (4.72 ± 5.85%; main predators chaetognaths and medusae). These results emphasize the important role of sea ice as a suitable winter habitat for larval krill with fewer competitors and lower predation risk. These benefits should be taken into account when considering the response of Antarctic krill to projected declines in sea ice. Whether reduced sea-ice algal production may be compensated for by increased water column production remains unclear, but the shelter provided by sea ice would be significantly reduced or disappear, thus increasing the predation risk on krill larvae.
Keywords: Sørishavet; krill; marin biologi; zooplankton

Interactive effects of body mass changes and species-specific morphology on flight behavior of chick-rearing Antarctic fulmarine petrels under diurnal wind patterns - Dehnhard, Nina; Klekociuk, Andrew R; Emmerson, Louise (Ecology and Evolution, 2021)
For procellariiform seabirds, wind and morphology are crucial determinants of flight costs and flight speeds. During chick-rearing, parental seabirds commute frequently to provision their chicks, and their body mass typically changes between outbound and return legs. In Antarctica, the characteristic diurnal katabatic winds, which blow stronger in the mornings, form a natural experimental setup to investigate flight behaviors of commuting seabirds in response to wind conditions. We GPS-tracked three closely related species of sympatrically breeding Antarctic fulmarine petrels, which differ in wing loading and aspect ratio, and investigated their flight behavior in response to wind and changes in body mass. Such information is critical for understanding how species may respond to climate change. All three species reached higher ground speeds (i.e., the speed over ground) under stronger tailwinds, especially on return legs from foraging. Ground speeds decreased under stronger headwinds. Antarctic petrels (Thalassoica antarctica; intermediate body mass, highest wing loading, and aspect ratio) responded stronger to changes in wind speed and direction than cape petrels (Daption capense; lowest body mass, wing loading, and aspect ratio) or southern fulmars (Fulmarus glacialoides; highest body mass, intermediate wing loading, and aspect ratio). Birds did not adjust their flight direction in relation to wind direction nor the maximum distance from their nests when encountering headwinds on outbound commutes. However, birds appeared to adjust the timing of commutes to benefit from strong katabatic winds as tailwinds on outbound legs and avoid strong katabatic winds as headwinds on return legs. Despite these adaptations to the predictable diurnal wind conditions, birds frequently encountered unfavorably strong headwinds, possibly as a result of weather systems disrupting the katabatics. How the predicted decrease in Antarctic near-coastal wind speeds over the remainder of the century will affect flight costs and breeding success and ultimately population trajectories remains to be seen.
Keywords: Antarktis; fôring; klimaendringer; ornitologi; petreller; zoologi; økofysiologi; økologi

Svarthamaren seabirds, sentinels of the Southern Ocean - Descamps, Sébastien; Moreau, Sébastien; Tarroux, Arnaud; Lorensten, Svein-Håkon; Bustnes, Jan-Ove; Yoccoz, Nigel G; Borgå, Katrine; Carravieri, Alice; Patrick, Samantha (Fram forum, 2021)
Keywords: Sørishavet; forurensning; klimaendringer; marin biologi; marine økosystemer; miljøendringer; observasjoner; ornitologi; sjøfugler; zoologi; økologi

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Moving mountains - when rocks and fluids interact - Engvik, Ane K.; Elvevold, Synnøve; Myhre, Per Inge; Sunde, Øyvind; Austrheim, Håkon (Fram forum, 2021)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Handley, Jonathan; Rouyer, Marie-Morgane; Pearmain, Elizabeth J; Warwick-Evans, Victoria; Teschke, Katharina; Hinke, Jefferson T; Lynch, Heather; Emmerson, Louise; Southwell, Colin; Griffith, Gary; Cárdenas, César A; Franco, Aldina M A; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.
Keywords: Antarktis; Sørishavet; biodiversitet; klimaendringer; marin biologi; miljøvern

Evidence for a grounding line fan at the onset of a basal channel under the ice shelf of Support Force Glacier, Antarctica, revealed by reflection seismics - Hofstede, Coen; Beyer, Sebastian; Corr, Hugh; Eisen, Olaf; Hattermann, Tore; Helm, Veit; Neckel, Niklas; Smith, Emma C; Steinhage, Daniel; Zeising, Ole; Humbert, Angelika (The Cryosphere, 2021)
Curvilinear channels on the surface of an ice shelf indicate the presence of large channels at the base. Modelling studies have shown that where these surface expressions intersect the grounding line, they coincide with the likely outflow of subglacial water. An understanding of the initiation and the ice–ocean evolution of the basal channels is required to understand the present behaviour and future dynamics of ice sheets and ice shelves. Here, we present focused active seismic and radar surveys of a basal channel, ∼950 m wide and ∼200 m high, and its upstream continuation beneath Support Force Glacier, which feeds into the Filchner Ice Shelf, West Antarctica. Immediately seaward from the grounding line, below the basal channel, the seismic profiles show an ∼6.75 km long, 3.2 km wide and 200 m thick sedimentary sequence with chaotic to weakly stratified reflections we interpret as a grounding line fan deposited by a subglacial drainage channel directly upstream of the basal channel. Further downstream the seabed has a different character; it consists of harder, stratified consolidated sediments, deposited under different glaciological circumstances, or possibly bedrock. In contrast to the standard perception of a rapid change in ice shelf thickness just downstream of the grounding line, we find a flat topography of the ice shelf base with an almost constant ice thickness gradient along-flow, indicating only little basal melting, but an initial widening of the basal channel, which we ascribe to melting along its flanks. Our findings provide a detailed view of a more complex interaction between the ocean and subglacial hydrology to form basal channels in ice shelves.
Keywords: Antarktis; geovitenskap; glasiologi; isshelf

FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea - Janout, Markus A; Hellmer, Hartmut H; Hattermann, Tore; Huhn, Oliver; Sültenfuss, Jürgen; Østerhus, Svein; Stulic, Lukrecia; Ryan, Svenja; Schröder, Michael; Kanzow, Torsten (Journal of Geophysical Research: Oceans, 2021)
The Filchner-Ronne Ice Shelf (FRIS) is characterized by moderate basal melt rates due to the near-freezing waters that dominate the wide southern Weddell Sea continental shelf. We revisited the region in austral summer 2018 with detailed hydrographic and noble gas surveys along FRIS. The FRIS front was characterized by High Salinity Shelf Water (HSSW) in Ronne Depression, Ice Shelf Water (ISW) on its eastern flank, and an inflow of modified Warm Deep Water (mWDW) entering through Central Trough. Filchner Trough was dominated by Ronne HSSW-sourced ISW, likely forced by a recently intensified circulation beneath FRIS due to enhanced sea ice production in the Ronne polynya since 2015. Glacial meltwater fractions and tracer-based water mass dating indicate two separate ISW outflow cores, one hugging the Berkner slope after a two-year travel time, and the other located in the central Filchner Trough following a ∼six year-long transit through the FRIS cavity. Historical measurements indicate the presence of two distinct modes, in which water masses in Filchner Trough were dominated by either Ronne HSSW-derived ISW (Ronne-mode) or more locally derived Berkner-HSSW (Berkner-mode). While the dominance of these modes has alternated on interannual time scales, ocean densities in Filchner Trough have remained remarkably stable since the first surveys in 1980. Indeed, geostrophic velocities indicated outflowing ISW-cores along the trough's western flank and onto Berkner Bank, which suggests that Ronne-ISW preconditions Berkner-HSSW production. The negligible density difference between Berkner- and Ronne-mode waters indicates that each contributes cold dense shelf waters to protect FRIS against inflowing mWDW.
Keywords: Sørishavet; Weddellhavet; oseanografi; vannmasser

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Evaluation of Three Numerical Weather Prediction Models for the Weddell Sea Region for the Austral Winter 2013 - Jonassen, Marius O; Nygård, Tiina; Vihma, Timo (Journal of Geophysical Research: Atmospheres, 2021)
It is widely recognized that numerical weather prediction (NWP) results for the Antarctic are relatively poor compared to the mid-latitudes. In this study, we evaluate output from three operational NWP systems: the ECMWF, Global Forecast System (GFS) and Antarctic Mesoscale Prediction System (AMPS), for the Austral winter (June-August) of 2013 for the Weddell Sea region, paying special attention to regional patterns of error statistics. This is the first evaluation of NWP systems over the Southern Ocean that also addresses the accuracy of forecasted vertical profiles. In the evaluation, we use data from land- and ship-based automatic weather stations (AWS) and radiosoundings. While the ECMWF and AMPS forecasts are on average biased cold and dry near the surface, the GFS forecasts are on average biased warm and moist. The near-surface wind speed is on average overestimated by the AMPS forecasts, whereas it is slightly underestimated by the forecasts of the other two NWP systems. Among the variables investigated, all three NWP systems forecast the near-surface specific humidity most accurately, followed by the temperature and then the wind speed. The forecast quality for the near-surface and upper-air wind speed degrades the most rapidly with increasing lead time, compared to the other variables. ECMWF is the overall best NWP system when compared against both the near-surface and upper-air observations, followed by AMPS and then GFS. The generally poorest model performance is found in locations with complex terrain along the coast of the Antarctic continent, and the best over the ocean.
Keywords: Sørishavet; Weddellhavet; geofysikk; meteorologi

Phenology and Environmental Control of Phytoplankton Blooms in the Kong Håkon VII Hav in the Southern Ocean - Kauko, Hanna M; Hattermann, Tore; Ryan-Keogh, Thomas; Singh, Asmita; de Steur, Laura; Fransson, Agneta; Chierici, Melissa; Falkenhaug, Tone; Hallfredsson, Elvar H; Bratbak, Gunnar; Tsagaraki, Tatiana; Berge, Terje; et al. (Frontiers in Marine Science, 2021)
Knowing the magnitude and timing of pelagic primary production is important for ecosystem and carbon sequestration studies, in addition to providing basic understanding of phytoplankton functioning. In this study we use data from an ecosystem cruise to Kong Håkon VII Hav, in the Atlantic sector of the Southern Ocean, in March 2019 and more than two decades of satellite-derived ocean color to study phytoplankton bloom phenology. During the cruise we observed phytoplankton blooms in different bloom phases. By correlating bloom phenology indices (i.e., bloom initiation and end) based on satellite remote sensing to the timing of changes in environmental conditions (i.e., sea ice, light, and mixed layer depth) we studied the environmental factors that seemingly drive phytoplankton blooms in the area. Our results show that blooms mainly take place in January and February, consistent with previous studies that include the area. Sea ice retreat controls the bloom initiation in particular along the coast and the western part of the study area, whereas bloom end is not primarily connected to sea ice advance. Light availability in general is not appearing to control the bloom termination, neither is nutrient availability based on the autumn cruise where we observed non-depleted macronutrient reservoirs in the surface. Instead, we surmise that zooplankton grazing plays a potentially large role to end the bloom, and thus controls its duration. The spatial correlation of the highest bloom magnitude with marked topographic features indicate that the interaction of ocean currents with sea floor topography enhances primary productivity in this area, probably by natural fertilization. Based on the bloom timing and magnitude patterns, we identified five different bloom regimes in the area. A more detailed understanding of the region will help to highlight areas with the highest relevance for the carbon cycle, the marine ecosystem and spatial management. With this gained understanding of bloom phenology, it will also be possible to study potential shifts in bloom timing and associated trophic mismatch caused by environmental changes.
Keywords: Sørishavet; fytoplankton; havis; marin biologi; marine økosystemer; miljøendringer; planteplankton; sjøis

Antarctic krill (Euphausia superba) exhibit positive phototaxis to white LED light - Krafft, Bjørn A; Krag, Ludvig A (Polar Biology, 2021)
Keywords: Sørishavet; fototaxis; krill; marin biologi; plankton

Standing stock of Antarctic krill (Euphausia superba Dana, 1850) (Euphausiacea) in the Southwest Atlantic sector of the Southern Ocean, 2018–19 - Krafft, Bjørn A; Macaulay, Gavin J; Skaret, Georg; Knutsen, Tor; Bergstad, Odd A; Lowther, Andrew; Huse, Geir; Fielding, Sophie; Trathan, Philip; Murphy, Eugene; Choi, Seok-Gwan; Chung, Sangdeok; et al. (Journal of Crustacean Biology, 2021)
Estimates of the distribution and density of Antarctic krill (Euphausia superba Dana, 1850) were derived from a large-scale survey conducted during the austral summer in the Southwest Atlantic sector of the Southern Ocean and across the Scotia Sea in 2018–19, the ‘2018–19 Area 48 Survey’. Survey vessels were provided by Norway, the Association of Responsible Krill harvesting companies and Aker BioMarine AS, the United Kingdom, Ukraine, Republic of Korea, and China. Survey design followed the transects of the Commission for the Conservation of Antarctic Marine Living Resources synoptic survey, carried out in 2000 and from regular national surveys performed in the South Atlantic sector by the U.S., China, Republic of Korea, Norway, and the U.K. The 2018–19 Area 48 Survey represents only the second large-scale survey performed in the area and this joint effort resulted in the largest ever total transect line (19,500 km) coverage carried out as one single exercise in the Southern Ocean. We delineated and integrated acoustic backscatter arising from krill swarms to produce distribution maps of krill areal biomass density and standing stock (biomass) estimates. Krill standing stock for the Area 48 was estimated to be 62.6 megatonnes (mean density of 30 g m–2 over 2 million km2) with a sampling coefficient variation of 13%. The highest mean krill densities were found in the South Orkney Islands stratum (93.2 g m–2) and the lowest in the South Georgia Island stratum (6.4 g m–2). The krill densities across the strata compared to those found during the previous survey indicate some regional differences in distribution and biomass. It is currently not possible to assign any such differences or lack of differences between the two survey datasets to longer term trends in the environment, krill stocks or fishing pressure.
Keywords: Sørishavet; krill; marin biologi; marine økosystemer; plankton

Subglacial discharge weakens the stability of the Ross Ice Shelf around the grounding line - Li, Yan; Shi, Hongling; Lu, Yang; Zhang, Zizhan; Xi, Hui (Polar Research, 2021)
In this paper, we examine potential impact of discharge in Subglacial Lake Engelhardt, West Antarctica, on the stability of the Ross Ice Shelf around the grounding line by combining satellite altimetry and remote sensing images. According to satellite altimetry data from the Ice, Cloud and Land Elevation Satellite (ICESat; 2003–06), Subglacial Lake Engelhardt (SLE) discharged ca. 1.91 ± 0.04 km3 of water into the downstream region. The ice-surface record derived from ICESat (2006–09) and CryoSat-2 (2011–17) data shows that the lake gained ca. 2.09 ± 0.05 km3 of water during the refilling event following the drainage event, taking three times as much time to reach the previous water level before the discharge; the calculation demonstrates that water input from an upstream lake is unable to sustain water increase in SLE, indicating that the subglacial, hydrologic system and groundwater flow could have contributed to water increase in SLE via hydrologic networks. Satellite images captured surface depressions and crevasses at the drainage outlet point of hydrologic networks around the grounding line; satellite altimetry data show that the ice surface there is still depressing even though the subglacial discharge has finished, potentially reflecting the long-term impact of subglacial discharge on the stability of the immediate Ross Ice Shelf around the grounding line. Keywords: Antarctic subglacial lakes; water storage change; satellite altimetry; remote sensing; hydraulic potential method.
Keywords: Antarktis; geodesi; hydrologi; isbreer; satellitt bilder; subglasial innsjø

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Antarctic krill Euphausia superba: spatial distribution, abundance, and management of fisheries in a changing climate - McBride, Margaret M; Schram Stokke, Olav; Renner, Angelika H H; Krafft, Bjørn A; Bergstad, Odd A; Biuw, Martin; Lowther, Andrew D; Stiansen, Jan E (Marine Ecology Progress Series, 2021)
Antarctic krill Euphausia superba, a keystone species in the Southern Ocean, is highly relevant for studying effects of climate-related shifts on management systems. Krill provides a key link between primary producers and higher trophic levels and supports the largest regional fishery. Any major perturbation in the krill population would have severe ecological and economic ramifications. We review the literature to determine how climate change, in concert with other environmental changes, alters krill habitat, affects spatial distribution/abundance, and impacts fisheries management. Findings recently reported on the effects of climate change on krill distribution and abundance are inconsistent, however, raising questions regarding methods used to detect changes in density and biomass. One recent study reported a sharp decline in krill densities near their northern limit, accompanied by a poleward contraction in distribution in the Southwest Atlantic sector. Another recent study found no evidence of long-term decline in krill density or biomass and reported no evidence of a poleward shift in distribution. Moreover, with predicted decreases in phytoplankton production, vertical foraging migrations to the seabed may become more frequent, also impacting krill production and harvesting. Potentially cumulative impacts of climate change further compound the management challenge faced by CCAMLR, the organization responsible for conservation of Antarctic marine living resources: to detect changes in the abundance, distribution, and reproductive performance of krill and krill-dependent predator stocks and to respond to such change by adjusting its conservation measures. Based on CCAMLR reports and documents, we review the institutional framework, outline how climate change has been addressed within this organization, and examine the prospects for further advances toward ecosystem risk assessment and an adaptive management system.
Keywords: Sørishavet; fiskeri; klimaendringer; marin biologi; zooplankton; økosystemer

Hemispheric black carbon increase after the 13th-century Māori arrival in New Zealand - McConnell, Joseph R; Chellman, Nathan J; Mulvaney, Robert; Eckhardt, Sabine; Stohl, Andreas; Plunkett, Gill; Kipfstuhl, Sepp; Freitag, Johannes; Isaksson, Elisabeth; Gleason, Kelly E; Brugger, Sandra O; McWethy, David B; et al. (Nature, 2021)
New Zealand was among the last habitable places on earth to be colonized by humans. Charcoal records indicate that wildfires were rare prior to colonization and widespread following the 13th- to 14th-century Māori settlement, but the precise timing and magnitude of associated biomass-burning emissions are unknown, as are effects on light-absorbing black carbon aerosol concentrations over the pristine Southern Ocean and Antarctica. Here we used an array of well-dated Antarctic ice-core records to show that while black carbon deposition rates were stable over continental Antarctica during the past two millennia, they were approximately threefold higher over the northern Antarctic Peninsula during the past 700 years. Aerosol modelling demonstrates that the observed deposition could result only from increased emissions poleward of 40° S—implicating fires in Tasmania, New Zealand and Patagonia—but only New Zealand palaeofire records indicate coincident increases. Rapid deposition increases started in 1297 (±30 s.d.) in the northern Antarctic Peninsula, consistent with the late 13th-century Māori settlement and New Zealand black carbon emissions of 36 (±21 2 s.d.) Gg y−1 during peak deposition in the 16th century. While charcoal and pollen records suggest earlier, climate-modulated burning in Tasmania and southern Patagonia, deposition in Antarctica shows that black carbon emissions from burning in New Zealand dwarfed other preindustrial emissions in these regions during the past 2,000 years, providing clear evidence of large-scale environmental effects associated with early human activities across the remote Southern Hemisphere.
Keywords: Antarktis; iskjerner; miljø; paleoklimatologi

Southern Ocean Food Web Modelling: Progress, Prognoses, and Future Priorities for Research and Policy Makers - McCormack, Stacey A; Melbourne-Thomas, Jessica; Trebilco, Rowan; Griffith, Gary; Hill, Simeon L; Hoover, Carie; Johnston, Nadine M; Marina, Tomás I; Murphy, Eugene J; Pakhomov, Evgeny A; Pinkerton, Matt; Plagányi, Éva; et al. (Frontiers in Ecology and Evolution, 2021)
Globally important services are supported by Southern Ocean ecosystems, underpinned by the structure, function, and dynamics of complex interconnected and regionally distinctive food webs. These food webs vary in response to a combination of physical and chemical processes that alter productivity, species composition and the relative abundance and dynamics of organisms. Combined with regional and seasonal variability, climate-induced changes and human activities have and are expected to continue to drive important structural and functional changes to Southern Ocean food webs. However, our current understanding of food web structure, function, status, and trends is patchy in space and time, and methods for systematically assessing and comparing community-level responses to change within and across regional and temporal scales are not well developed. Insights gained from food web modelling studies—ranging from theoretical analyses of ecosystem resilience and adaptation, to qualitative and quantitative descriptions of the system—can assist in resolving patterns of energy flow and the ecological mechanisms that drive food web structure, function, and responses to drivers (such as fishing and climate change). This understanding is required to inform robust management strategies to conserve Southern Ocean food webs and the ecosystem services they underpin in the face of change. This paper synthesises the current state of knowledge regarding Southern Ocean pelagic food webs, highlighting the distinct regional food web characteristics, including key drivers of energy flow, dominant species, and network properties that may indicate system resilience. In particular, the insights, gaps, and potential integration of existing knowledge and Southern Ocean food web models are evaluated as a basis for developing integrated food web assessments that can be used to test the efficacy of alternative management and policy options. We discuss key limitations of existing models for assessing change resulting from various drivers, summarise priorities for model development and identify that significant progress could be made to support policy by advancing the development of food web models coupled to projected biogeochemical models, such as in Earth System models.
Keywords: Sørishavet; marin biologi; marine økosystemer

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Variability of Sea-Air Carbon Dioxide Flux in Autumn Across the Weddell Gyre and Offshore Dronning Maud Land in the Southern Ocean - Ogundare, Margaret Ojone; Fransson, Agneta; Chierici, Melissa; Joubert, Warren R.; Roychoudhury, Alakendra N. (Frontiers in Marine Science, 2021)
Sea surface fugacity of carbon dioxide (fCO2ssw) was measured across the Weddell gyre and the eastern sector in the Atlantic Southern Ocean in autumn. During the occupation between February and April 2019, the region of the study transect was a potential ocean CO2 sink. A net CO2 flux (FCO2) of −6.2 (± 8; sink) mmol m–2 d–1 was estimated for the entire study region, with the largest average CO2 sink of −10.0 (± 8) mmol m–2 d–1 in the partly ice-covered Astrid Ridge (AR) region near the coast at 68°S and −6.1 (± 8) mmol m–2d–1 was observed in the Maud Rise (MR) region. A CO2 sink was also observed south of 66°S in the Weddell Sea (WS). To assess the main drivers describing the variability of fCO2ssw, a correlation model using fCO2 and oxygen saturation was considered. Spatial distributions of the fCO2 saturation/O2 saturation correlations, described relative to the surface water properties of the controlling variables (chlorophyll a, apparent oxygen utilization (AOU), sea surface temperature, and sea surface salinity) further constrained the interplay of the processes driving the fCO2ssw distributions. Photosynthetic CO2 drawdown significantly offsets the influence of the upwelling of CO2-rich waters in the central Weddell gyre and enhanced the CO2 sink in the region. FCO2 of −6.9 mmol m–2 d–1 estimated for the Weddell gyre in this study was different from FCO2 of −2.5 mmol m–2 d–1 in autumn estimated in a previous study. Due to low CO2 data coverage during autumn, limited sea-air CO2 flux estimates from direct sea-surface CO2 observations particularly for the Weddell gyre region are available with which to compare the values estimated in this study. This highlights the importance of increasing seasonal CO2 observations especially during autumn/winter to improving the seasonal coverage of flux estimates in the seasonal sea ice-covered regions of the Southern Ocean.
Keywords: Sørishavet; karbondioksid; kjemi

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Evidence for the Impact of Climate Change on Primary Producers in the Southern Ocean - Pinkerton, Matthew H; Boyd, Philip W; Deppeler, Stacy; Hayward, Alex; Höfer, Juan; Moreau, Sebastien (Frontiers in Ecology and Evolution, 2021)
Within the framework of the Marine Ecosystem Assessment for the Southern Ocean (MEASO), this paper brings together analyses of recent trends in phytoplankton biomass, primary production and irradiance at the base of the mixed layer in the Southern Ocean and summarises future projections. Satellite observations suggest that phytoplankton biomass in the mixed-layer has increased over the last 20 years in most (but not all) parts of the Southern Ocean, whereas primary production at the base of the mixed-layer has likely decreased over the same period. Different satellite models of primary production (Vertically Generalised versus Carbon Based Production Models) give different patterns and directions of recent change in net primary production (NPP). At present, the satellite record is not long enough to distinguish between trends and climate-related cycles in primary production. Over the next 100 years, Earth system models project increasing NPP in the water column in the MEASO northern and Antarctic zones but decreases in the Subantarctic zone. Low confidence in these projections arises from: (1) the difficulty in mapping supply mechanisms for key nutrients (silicate, iron); and (2) understanding the effects of multiple stressors (including irradiance, nutrients, temperature, pCO2, pH, grazing) on different species of Antarctic phytoplankton. Notwithstanding these uncertainties, there are likely to be changes to the seasonal patterns of production and the microbial community present over the next 50–100 years and these changes will have ecological consequences across Southern Ocean food-webs, especially on key species such as Antarctic krill and silverfish.
Keywords: Sørishavet; biogeokjemi; fytoplankton; klimaendringer; marine økosystemer; phytoplankton

Internal Ocean Dynamics Control the Long-Term Evolution of Weddell Sea Polynya Activity - Rheinlænder, Jonathan W.; Smedsrud, Lars H.; Nisanciouglu, Kerim H. (Frontiers in Climate, 2021)
Open-ocean polynyas effectively couple the ocean and atmosphere through large ice-free areas within the sea-ice cover, release vast quantities of oceanic heat, and impact deep ocean ventilation. Changes in polynya activity, particularly in the Weddell Sea, may be key to longer time-scale climate fluctuations, feedbacks and abrupt change. While changes in the occurrence of Weddell Sea polynyas are generally attributed to changes in the atmospheric surface forcing, the role of internal ocean dynamics for polynya variability is not well-resolved. In this study we employ a global coupled ocean-sea ice model with a repeating annual atmospheric cycle to explore changes in Weddell Sea water mass properties, stratification and ocean circulation driven by open-ocean polynyas. During the 1300-year long simulation, two large polynyas occur in the central Weddell Sea. Our results suggest that Weddell polynyas may be triggered without inter-annual changes in the atmospheric forcing. This highlights the role of ocean processes in preconditioning and triggering open-ocean polynyas on multi-centennial time-scales. The simulated polynyas form due to internal ocean-sea ice dynamics associated with a slow build-up and subsequent release of subsurface heat. A strong stratification and weak vertical mixing is necessary for building the subsurface heat reservoir. Once the water column turns unstable, enhanced vertical mixing of warm and saline waters into the surface layer causes efficient sea ice melt and the polynya appears. Subsequent, vigorous deep convection is maintained through upwelling of warm deep water leading to enhanced bottom water formation. We find a cessation of simulated deep convection and polynya activity due to long-term cooling and freshening of the subsurface heat reservoir. As subsurface waters in the Southern Ocean are now becoming warmer and saltier, we speculate that larger and more persistent Weddell polynyas could become more frequent in the future.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; polynja; sjøis

Icebreaking polar class research vessels: New Antarctic fleet capabilities - Rogan-Finnemore, Michelle; Ojeda, Miguel; Paz Acosta, Jorge Manuel; Bretel, Patrice; Browne, Nick; Flått, Stig; Shuoren, Wang; Sliester, Randolph (Polar Record, 2021)
Supporting Antarctic scientific investigation is the job of the national Antarctic programmes, the government entities charged with delivering their countries’ Antarctic research strategies. This requires sustained investment in people, innovative technologies, Antarctic infrastructures, and vessels with icebreaking capabilities. The recent endorsement of the International Maritime Organization (IMO) Polar Code (2015) means that countries must address challenges related to an ageing icebreaking vessel fleet. Many countries have recently invested in and begun, or completed, builds on new icebreaking Polar research vessels. These vessels incorporate innovative technologies to increase fuel efficiency, to reduce noise output, and to address ways to protect the Antarctic environment in their design. This paper is a result of a Council of Managers of National Antarctic Programs (COMNAP) project on new vessel builds which began in 2018. It considers the recent vessel builds of Australia’s RSV Nuyina, China’s MV Xue Long 2, France’s L’Astrolabe, Norway’s RV Kronprins Haakon, Peru’s BAP Carrasco, and the United Kingdom’s RRS Sir David Attenborough. The paper provides examples of purposeful consideration of science support requirements and environmental sustainability in vessel designs and operations.
Keywords: Sørishavet; skipsfart; teknologi

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Substantial spatial variation in glacial erosion rates in the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna K (Communications Earth & Environment, 2021)
The coast-parallel Dronning Maud Land (DML) mountains represent a key nucleation site for the protracted glaciation of Antarctica. Their evolution is therefore of special interest for understanding the formation and development of the Antarctic ice sheet. Extensive glacial erosion has clearly altered the landscape over the past 34 Myr. Yet, the total erosion still remains to be properly constrained. Here, we investigate the power of low-temperature thermochronology in quantifying glacial erosion in-situ. Our data document the differential erosion along the DML escarpment, with up to c. 1.5 and 2.4 km of erosion in western and central DML, respectively. Substantial erosion at the escarpment foothills, and limited erosion at high elevations and close to drainage divides, is consistent with an escarpment retreat model. Such differential erosion suggests major alterations of the landscape during 34 Myr of glaciation and should be implemented in future ice sheet models.
Keywords: Dronning Maud Land; geologi; geomorfologi

Antarctic icebergs reorganize ocean circulation during Pleistocene glacials - Starr, Aidan; Hall, Ian R.; Barker, Stephen; Rackow, Thomas; Zhang, Xu; Hemming, Sidney R.; van der Lubbe, H. J. L.; Knorr, Gregor; Berke, Melissa A.; Bigg, Grant R.; Cartagena-Sierra, Alejandra; Jiménez-Espejo, Francisco J.; et al. (Nature, 2021)
The dominant feature of large-scale mass transfer in the modern ocean is the Atlantic meridional overturning circulation (AMOC). The geometry and vigour of this circulation influences global climate on various timescales. Palaeoceanographic evidence suggests that during glacial periods of the past 1.5 million years the AMOC had markedly different features from today1; in the Atlantic basin, deep waters of Southern Ocean origin increased in volume while above them the core of the North Atlantic Deep Water (NADW) shoaled2. An absence of evidence on the origin of this phenomenon means that the sequence of events leading to global glacial conditions remains unclear. Here we present multi-proxy evidence showing that northward shifts in Antarctic iceberg melt in the Indian–Atlantic Southern Ocean (0–50° E) systematically preceded deep-water mass reorganizations by one to two thousand years during Pleistocene-era glaciations. With the aid of iceberg-trajectory model experiments, we demonstrate that such a shift in iceberg trajectories during glacial periods can result in a considerable redistribution of freshwater in the Southern Ocean. We suggest that this, in concert with increased sea-ice cover, enabled positive buoyancy anomalies to ‘escape’ into the upper limb of the AMOC, providing a teleconnection between surface Southern Ocean conditions and the formation of NADW. The magnitude and pacing of this mechanism evolved substantially across the mid-Pleistocene transition, and the coeval increase in magnitude of the ‘southern escape’ and deep circulation perturbations implicate this mechanism as a key feedback in the transition to the ‘100-kyr world’, in which glacial–interglacial cycles occur at roughly 100,000-year periods.
Keywords: Sørishavet; havstrømmer; isfjell; paleoklimatologi; paleoseanografi

Climate change impacts on sea-ice ecosystems and associated ecosystem services - Steiner, Nadja S; Bowman, Jeff; Campbell, Karley; Chierici, Melissa; Eronen-Rasimus, Eeva; Falardeau, Marianne; Flores, Hauke; Fransson, Agneta; Herr, Helena; Insley, Stephen J; Kauko, Hanna M; Lannuzel, Delphine; et al. (Elementa: Science of the Anthropocene, 2021)
A rigorous synthesis of the sea-ice ecosystem and linked ecosystem services highlights that the sea-ice ecosystem supports all 4 ecosystem service categories, that sea-ice ecosystems meet the criteria for ecologically or biologically significant marine areas, that global emissions driving climate change are directly linked to the demise of sea-ice ecosystems and its ecosystem services, and that the sea-ice ecosystem deserves specific attention in the evaluation of marine protected area planning. The synthesis outlines (1) supporting services, provided in form of habitat, including feeding grounds and nurseries for microbes, meiofauna, fish, birds and mammals (particularly the key species Arctic cod, Boreogadus saida, and Antarctic krill, Euphausia superba, which are tightly linked to the sea-ice ecosystem and transfer carbon from sea-ice primary producers to higher trophic level fish, mammal species and humans); (2) provisioning services through harvesting and medicinal and genetic resources; (3) cultural services through Indigenous and local knowledge systems, cultural identity and spirituality, and via cultural activities, tourism and research; (4) (climate) regulating services through light regulation, the production of biogenic aerosols, halogen oxidation and the release or uptake of greenhouse gases, for example, carbon dioxide. The ongoing changes in the polar regions have strong impacts on sea-ice ecosystems and associated ecosystem services. While the response of sea-ice–associated primary production to environmental change is regionally variable, the effect on ice-associated mammals and birds is predominantly negative, subsequently impacting human harvesting and cultural services in both polar regions. Conservation can help protect some species and functions. However, the key mitigation measure that can slow the transition to a strictly seasonal ice cover in the Arctic Ocean, reduce the overall loss of sea-ice habitats from the ocean, and thus preserve the unique ecosystem services provided by sea ice and their contributions to human well-being is a reduction in carbon emissions.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer

An ocean of possibilities: antarctic petrel's foraging in the Southern Ocean - Tarroux, Arnaud; Fauchald, Per; Varpe, Øystein; Yoccoz, Nigel G; Descamps, Sébastien (Fram forum, 2021)
Keywords: Sørishavet; fôring; marin biologi; observasjoner; ornitologi; petreller; sjøfugler; zoologi

Linking Sub-Tropical Evaporation and Extreme Precipitation Over East Antarctica: An Atmospheric River Case Study - Terpstra, Annick; Gorodetskaya, Irina V; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2021)
We investigate an intense snowfall event between 15 and 18 February 2011 over the East Antarctic coastal region which contributed to roughly 24% of the annual snow accumulation. The event was previously associated with an atmospheric river, and here we use both Eulerian and Lagrangian analysis to gain an understanding of the processes contributing to the atmospheric river signature. The planetary-scale configuration during the event consisted of a persistent blocking situation resulting in a sustained meridional flow from the sub-tropics to the Antarctic ice sheet between 20 and 50°E. Within this configuration, synoptic-scale cyclogenesis contributed to slantwise ascent of moisture loaded air parcels toward Antarctica. Landfall of this cyclone’s warm sector coincided with the onset of Antarctic precipitation. Subsequently, a secondary cyclone developed along a pre-existing baroclinic zone. The rapid intensification and propagation speed of this mesoscale cyclone alongside the warm, moist air mass resulted in strong moisture flux convergence ahead of the cyclone, providing additional poleward moisture transport. The poleward progression of warm moist air and a corresponding decrease of sea-surface temperatures implied downward surface sensible and latent heat fluxes throughout the region of intense poleward moisture, roughly between 40 and 60°S. Hence, moisture uptake via surface evaporation was suppressed between the sub-tropics and the polar continent, favoring long-range transport. Identification of the surface moisture uptake region by tracing changes in moisture in air parcels confirmed the limited uptake of moisture during the poleward transport in this case study, with the primary moisture source for Antarctic precipitation located in the sub-tropics.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; meteorologi; nedbør; snøfall

Satellite and ground based estimates for ice surface velocities in the part of central Dronning Maud Land, East Antarctica: Implications for ice flux calculations - Thakur, Praveen K; Swain, Ashit K; Dhote, Pankaj R; Kumar, Pradeep; Kaushik, Suvrat; Gajbhiye, Deepak; Mahagaonkar, Anirudha; Sharma, Vishal; Dharwadkar, Amit; Aggarwal, S P; Beg, Javed; Chauhan, Prakash; et al. (Polar Science, 2021)
The ice sheet and glaciers of Antarctica and Greenland represent the largest sources of freshwater on planet Earth. The understanding and quantification of their dynamic properties such as albedo, precipitation, ice mass movement, and ice elevation changes are critical for the improved climate and mass balance models. The present study utilizes space-borne optical and synthetic aperture radar (SAR) imagery to measure the ice surface velocity at high spatial resolution for a part of the central Dronning Maud Land (cDML), East Antarctica. The datasets from Landsat-8 and Sentinel-1 SAR satellite are used for ice stream velocity estimation using feature-offset tracking and differential interferometric SAR (DInSAR) methods. The derived velocity products are validated with ground based stakes network at annual time scale. The fundamental ice flow laws are used to estimate the ice outflux or discharge for selected ice stream drainage basins of cDML at fluxgate locations. The ice stream basin has been delineated using combination of elevation, slope and continental scale velocity maps. The ice influx for study area is estimated using ECMWF fifth generation reanalysis (ERA5) and Regional Atmospheric Climate Model (RACMO) v2.3 model outputs. The estimated influx and outflux are in the ranges of 0.18–4.167 Gt/y and 0.201 to 1.278 Gt/y respectively, indicating net positive mass balance for the selected area.
Keywords: Dronning Maud Land; glasiologi; innlandsis; polarområdene

Surface Mass Balance Controlled by Local Surface Slope in Inland Antarctica: Implications for Ice-Sheet Mass Balance and Oldest Ice Delineation in Dome Fuji - Van Liefferinge, Brice; Taylor, Drew; Tsutaki, Shun; Fujita, Shuji; Gogineni, Prasad; Kawamura, Kenji; Matsuoka, Kenichi; Moholdt, Geir; Oyabu, Ikumi; Abe-Ouchi, Ayako; Awasthi, Abhishek; Buizert, Christo; et al. (Geophysical Research Letters, 2021)
The limited number of surface mass balance (SMB) observations in the Antarctic inland hampers estimates of ice-sheet contribution to global sea level and locations with million-year-old ice. We present finely resolved SMB over the past three centuries in a low-accumulation region with significant depth hoar formation on Dome Fuji derived from ∼1,100 km of microwave radar stratigraphy dated with a firn core. The regional-mean SMB over the past 264 years is estimated to ∼22.5 ± 3.3 kg m−2 a−1, but with large local variability of up to 30%. We found that local SMB is negatively correlated with surface slope at scales of a few hundred meters, resulting in anomalous zones of low SMB which represent as much as 8–10% of the total SMB on the inland plateau if the SMB-slope relationship is more widely valid. This impact should be investigated further to improve estimates of Antarctic mass balance and sea-level contribution.
Keywords: Antarktis; glasiologi

Legitimacy of the Antarctic Treaty System: is it time for a reform? - Yermakova, Yelena (The Polar Journal, 2021)
The Antarctic Treaty System (ATS) has governed the Antarctic for the last six decades ensuring it to be a place of peace and scientific cooperation. Like any institution, the ATS exists in order to solve collective action problems through coordination and the creation of norms. But how do we know if a particular institution is the right one to solve a specific problem or address issues regarding the governance of a region? And when is it time to replace or reform such an institution? To answer these questions, we need an account of institutional legitimacy. An assessment of the legitimacy of the ATS is necessary in order to determine whether it is worthy of being empowered through support, or if it is time to reform some aspects of it. Building on the account of legitimacy of global governance institutions proposed by Buchanan and Keohane, the paper assesses the legitimacy of the ATS and argues that it is time to reform some components of it. Specifically, the paper assesses the legitimacy of the ATS based on the following criteria: minimal moral acceptability; comparative benefit; institutional integrity; and accountability. The paper highlights the ATS? shortcomings based on these criteria and suggests reforms that will strengthen the legitimacy of the ATS
Keywords: Antarktis; Antarktistraktaten